Exceeding Single‐Pass Equilibrium with Integrated Absorption Separation for Ammonia Synthesis Using Renewable Energy—Redefining the Haber‐Bosch Loop. Issue 13 (28th February 2021) - Smith, Collin; Torrente‐Murciano, Laura
Abstract: The synthesis of ammonia through the Haber‐Bosch process has been at the foundation of the chemical industry for over 100 years, but when the energy and feedstock sources switch from fossil fuels to renewable electricity, the process needs to be reimagined. Herein, the successful integration of ammonia synthesis and separation is demonstrated in a recycle‐less process setting the foundations of green ammonia technology. The ruthenium‐based catalyst uses a nanostructured CeO2 support and Cs electronic promotion to remove hydrogen and ammonia inhibition, respectively, creating a catalyst with low‐temperature (<300 °C) activity that quickly approaches equilibrium. The absorbent uses MnCl2 to avoid the acid releasing decomposition of conventional absorbents like MgCl2, and a support of SiO2 to simultaneously enhance MnCl2 dispersion and improve stabilization. This integrated catalyst‐absorbent system reproducibly exceeds single‐pass ammonia synthesis equilibrium. Kinetic models of the catalyst and absorbent successfully predict the experimental long‐term behavior and facilitate the design of an integrated system. These results present a framework for aligning intermittent and isolated renewable energy with ammonia synthesis by decreasing capital complexity and increasing process agility—adapting to a shifting energy landscape to continue providing fertilizers with minimum CO2 penalty and pioneer energy storage. Abstract : With a novel combination of catalyst and absorbent, the ability to exceed single‐pass equilibrium in one vessel is shown for the first time. A catalyst is designed to mitigate both H2 and NH3 inhibition, and a new absorbent with unique properties is implemented. Kinetic models of catalyst and absorbent reliably predict system performance and are used to explore process design.